Models for the substantiation of structure of decision making support system of the operator-director - Лавров, Евгений Анатольевич; Пасько, Надежда Борисовна (Eastern-European Journal of Enterprise Technologies, 2012)
The task of formalization of process of informative support of operator-director is examined. The model of decision-making support systems is developed for an operator-director. Made a decision about fixing functions after operators.